Thinking on Film and Trash: A Few Notes - Livon-Grosman, Ernesto (2015)
Latin american films have portrayed trash as an urban social issue since the 1940s, if not earlier. If the first incentive to film trash and its presence in the city was hygiene, very soon after that decade filmmakers began to depict the process of collecting trash as an activity that carries an important economic and social impact. In very early newsreels one could find some of the same informal recyclers that we can still see today, but in those images the rag picker is a lonely character walking or riding a carriage through the city far from the collective activity of today’s informal recycling. The number of documentaries today related to trash is vast and therefore this very short list of films is one of many possible ones.